Measurement of Fibrinogen Concentrations in Suspensions of Washed Rabbit and Human Platelets by Radioimmunoassays - Harfenist, Elizabeth J; Wrana, Jeffrey L; Packham, Marian A; Mustard, J Fraser (Thrombosis and Haemostasis, 1985)
Although fibrinogen is a cofactor in platelet aggregation, washed rabbit platelets aggregate when stimulated with ADP even when no fibrinogen is added to the platelet suspension. Washed human platelets usually do not aggregate to a significant extent when stimulated with ADP unless fibrinogen is added. To study this phenomenon, radioimmunoassays for rabbit and human fibrinogens have been developed and used to measure fibrinogen concentrations in suspensions of washed platelets. The fibrinogen concentration in the suspending medium of rabbit platelets was 2.5 ± 0.9 μg/109 platelets, and upon stimulation with 9 μM ADP it increased to 10.7 ± 2.9 μg/109 platelets. The loss of fibrinogen from the platelets was significantly greater than the loss of 14C-serotonin (11% vs 2%). The presence of prostaglandin E1 reduced the fibrinogen concentration to approximately 1 μg/109 platelets and prevented aggregation and loss of fibrinogen when the platelets were stimulated with ADP. With human platelets, the extracellular concentrations of fibrinogen and β-thromboglobulin, expressed as percentages of the amount in the platelets, were similar, and the increase in fibrinogen concentration upon ADP stimulation (approximately 2%) was much lower than with rabbit platelets. We conclude that rabbit platelets may release fibrinogen from their α-granules when stimulated with ADP, and that a portion of the released fibrinogen becomes available to support aggregation. Smaller amounts of fibrinogen would become available in the case of human platelets.
Keywords: Platelets; Fibrinogen; ADP; Radioimmunoassay